2016
DOI: 10.1039/c6fo00423g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fe-YM1504 on iron deficiency anemia in rats

Abstract: Iron deficiency anemia (IDA) is one of the most serious forms of malnutrition. It is possible that some strains present in the natural environment possess a higher tolerance to inorganic iron and a higher ability to convert and accumulate iron compared with Saccharomyces cerevisiae wild-type strain. In the present study, the strain no. YM1504, able to grow in an iron-rich environment, was used as a potential organic iron supplement, and its efficacy in alleviating IDA in rats was investigated. Sixty female wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 41 publications
(79 reference statements)
7
15
0
Order By: Relevance
“…However, in contrast to the liver and renal, no significant differences ( P > 0.05) were observed in the spleen coefficients of rats in different iron supplement groups and IDA group. This result was similar with that reported by Zhang et al . which confirmed that iron deficiency had no adverse effect on the spleen weight.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…However, in contrast to the liver and renal, no significant differences ( P > 0.05) were observed in the spleen coefficients of rats in different iron supplement groups and IDA group. This result was similar with that reported by Zhang et al . which confirmed that iron deficiency had no adverse effect on the spleen weight.…”
Section: Resultssupporting
confidence: 93%
“…MCH in all doses of iron supplements showed no significant differences ( P > 0.05) compared with the control group. This result was also observed by Zhang et al . The SI and SF levels in the model group were less than that of the control group ( P < 0.05, Fig.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Serum total iron binding capacity (TIBC) was determined using commercially available kits (Nanjing Jiancheng Bioengineering Institute, Nanjing, China). 30 The limit of detection of this kit was 0.05 mg L À1 .…”
Section: Hematological and Iron Analysismentioning
confidence: 92%